Tax Avoidance Affected By Audit Quality and Company Factors - Ananda, Priscila Della; Siahaan, Magda (Media Bisnis, 2024)
This study aims to obtain empirical evidence regarding the effect of the proportion of independent commissioners, audit committees, audit quality, profitability, company size, sales growth, institutional ownership, and leverage on tax avoidance. The sample used in this study were manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2021 with a purposive sampling method, resulting in 58 companies with 174 data. The data analysis method in this study used multiple regression analysis. The results of this study indicate that the proportion of independent commissioners, audit committees, audit quality, profitability, company size, sales growth, and institutional ownership do not affect tax avoidance. At the same time, leverage has a negative effect on tax avoidance.